A customizable component for low-level communication software - Santos, T.R.C.; Frohlich, A.A.F. (19th International Symposium on High Performance Computing Systems and Applications (HPCS'05), 2005)
This paper discusses the design of a customizable component that encapsulates a raw baseline communication architecture and a set of lightweight protocols. These protocols can act in specific points of the baseline architecture's algorithm in order tailor communication or provide new services according to the requirements of specific classes of applications. An implementation of the described component is currently being used by the application-oriented parallel programming environment SNOW, which provides specially tailored run-time systems for parallel applications running on dedicated clusters.